Genetic insights into the hypoxia-inducible factor (HIF) pathway. - Kiriakidis, S; Esteban, M; Maxwell, P (2007)
The HIF system probably operates in all cells, in all metazoan organisms. The effects of genetic alterations in the main components of the pathway offer a very powerful way to delineate its function in normal biology and disease. With time it is likely that more subtle variations will be identified in human populations, which are likely to be important in disease susceptibility. © 2006 Elsevier Ltd. All rights reserved.